Characteristics and outcome of infants with bronchopulmonary dysplasia established on long‐term ventilation from neonatal intensive care. Issue 11 (29th July 2022) - Ong, Jonathan Wen Yi; Everitt, Lucy; Hiscutt, Jodie; Griffiths, Catherine; McEvoy, Alison; Goss, Kevin Colin William; Johnson, Mark John; Evans, Hazel J.
Abstract: Introduction: Ex‐preterm infants with severe bronchopulmonary dysplasia (BPD) sometimes require long‐term ventilation (LTV) to facilitate weaning from respiratory support. There are however limited data characterizing this cohort. We aim to describe the background characteristics, neonatal comorbidities, characteristics at the initiation of ventilation, and outcomes of neonatal unit graduates with BPD established on LTV. Methods: A retrospective cohort study of infants born <32 weeks gestation with BPD referred to a regional LTV service between January 2015 and December 2020. Results: Twenty‐five infants were referred during the study period. Median birth gestation was 26 + 1 weeks (24 + 0–30 + 4) and birth weight 645 g (430–1485). At 36 weeks postmenstrual age (PMA), median FiO2 was 0.45 (0.24–0.80) and one‐quarter of infants remained on invasive ventilation. Twenty (80%) infants were established on noninvasive ventilation (NIV), with the smallest weighing 2085 g, and five (20%) required tracheostomy invasive ventilation (TIV). At initiation of NIV/TIV, median PMA was 41 + 1 weeks and median FiO2 0.40 (0.29–0.80). Infants established on TIV spent almost five times longer in hospital before discharge compared to those on NIV ( p  = 0.003). By March 2022, 18 (72%) infants had discontinued ventilation, spending a median total time of 113 days (18–1792) on ventilation. Conclusion: Due to advances in interfaces, headgear, and ventilator technology, NIV is an attractive and practically achievable option for infants with severe BPD as small as 2 kg. Initiation and weaning should take place in a facility with the required multidisciplinary expertize.